Class Struggle as the Impact of Oppression Seen in Clifford Odets’ Waiting for Lefty - Putra, Hardian; Widyastuti, Dewi (Journal of Language and Literature, 2014)
an oppressed class against the oppressor class to overthrow the throne of the oppressor class. In this case, the class of proletariat against the class of capitalists. The proletariat are engaged in this class struggle because they want welfare in their life. Waiting for Lefty, a play written by Clifford Odets which is often considered a masterpiece, has a theme related to class struggle. It talks so much about the gap that separates the two classes mentioned previously and also the oppression that comes along. This oppression is found in the form of economic and legal oppression and are responded by the oppressed class in the form of class struggle. The class struggle itself becomes a reality after the oppressed class experiences the class consciousness. The oppression and class struggle depicted in the play will be the main focus of this study. Thus, it will be relevant to analyze the class struggle as the impact of oppression in Waiting for Lefty by applying the theory of Marxism.Keywords: oppression, class struggle, Marxism